Retinal Lineage Therapeutic Specific Effect of Human Orbital and Abdominal Adipose-Derived Mesenchymal Stem Cells. (19th October 2021) - Krief, Bryan; Algor, Shira Weisthal; Nakdimon, Itay; Elhikis, Ayala; Benhamou, Moshe; Kadmon, Anouk Savir; Keren, Shay; Ohana, Oded; Feldman, Ilan; Cnaan, Ran Ben; Leibovitch, Igal; Loewenstein, Anat; et al.
Abstract : Retinal degenerative diseases are one of the main causes of complete blindness in aged population. In this study, we compared the therapeutic potential for retinal degeneration of human mesenchymal stem cells derived from abdominal subcutaneous fat (ABASCs) or from orbital fat (OASCs) due to their accessibility and mutual embryonic origin with retinal tissue, respectively. OASCs were found to protect RPE cells from cell death and were demonstrated to increase early RPE precursor markers, while ABASCs showed a raise in retinal precursor marker expression. Subretinal transplantation of OASCs in a mouse model of retinal degeneration led to restoration of the RPE layer while transplantation of ABASCs resulted in a significant restoration of the photoreceptor layer. Taken together, we demonstrated a lineage-specific therapeutic effect for either OASCs or ABASCs in retinal regeneration.